2020
DOI: 10.1186/s13756-020-00792-9
|View full text |Cite
|
Sign up to set email alerts
|

A rapid model for developing dry surface biofilms of Staphylococcus aureus and Pseudomonas aeruginosa for in vitro disinfectant efficacy testing

Abstract: Background: Bacterial biofilms persistent on dry environmental surfaces in healthcare facilities play an important role in the occurrence of healthcare associated infections (HAI). Compared to wet surface biofilms and planktonic bacteria, dry surface biofilms (DSB) are more tolerant to disinfection. However, there is no official method for developing DSB for in vitro disinfectant efficacy testing. The objectives of this study were to (i) develop an in vitro model of DSB of S. aureus and P. aeruginosa for disin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 47 publications
(78 reference statements)
3
38
0
Order By: Relevance
“…We found that mean log 10 densities per coupon from this study were comparable to the ranges previously reported by Nkemngong et al, 2020 [34]. We found that overall and irrespective of dry time, CL, SH, HP and QA disinfectants were signi cantly more bactericidal against DSB of S. aureus than QT disinfectants.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that mean log 10 densities per coupon from this study were comparable to the ranges previously reported by Nkemngong et al, 2020 [34]. We found that overall and irrespective of dry time, CL, SH, HP and QA disinfectants were signi cantly more bactericidal against DSB of S. aureus than QT disinfectants.…”
Section: Discussionsupporting
confidence: 90%
“…Our study found differences in the overall bactericidal e cacy of disinfectants against DSB of S. aureus and P. aeruginosa after prolonged dehydration for 24 h and 72 h. While there was no signi cant difference in log 10 reductions between 24 h and 72 h DSB of S. aureus, the reverse was true for DSB of P. aeruginosa as 72 h DSB of P. aeruginosa were harder to kill than their 24 h counterparts. In a previous study by our group, we found that 100% of P. aeruginosa DSB established at a dehydration temperature of 21°C were encased in EPS while this was true for only 92% of S. aureus DSB established at 25°C [34]. The consistent presence of EPS on DSB of P. aeruginosa at dehydration time points from 24 h to 120 h as previously demonstrated by our group suggested that older DSB of P. aeruginosa developed using our model may be encased in more EPS; making them harder to kill [34].…”
Section: Bactericidal E Cacy Varies By Strain After Prolonged Dehydramentioning
confidence: 79%
See 3 more Smart Citations